2001
DOI: 10.21307/immunohematology-2019-543
|View full text |Cite
|
Sign up to set email alerts
|

Acute hemolytic transfusion reaction caused by anti-Coa

Abstract: Co a is a high-frequency blood group antigen in the Colton blood group system expressed on red blood cells (RBCs) of approximately 99.8 percent of random persons. Anti-Co a has been reported to cause delayed hemolytic transfusion reactions, hemolytic disease of the newborn, and accelerated clearance of RBCs in vivo. Acute hemolytic transfusion reactions (AHTRs) have not previously been reported. A 58-year-old man was hospitalized for vascular surgery. Initial blood bank evaluation revealed anti-Fy a . The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Few reports of significant delayed or acute transfusion reactions or haemolytic disease of the foetus and newborn attributable to anti-Co a have been reported, although both are known to occur with severe morbidity; anti-Co b is relatively rare and often found in patient's sera containing other alloantibodies. In vivo studies have shown that anti-Co a and anti-Co b antibodies are able to reduce the survival of targeted erythrocytes [19][20][21][22][23]. There are also reports of auto-antibodies mimicking Colton specificities [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Few reports of significant delayed or acute transfusion reactions or haemolytic disease of the foetus and newborn attributable to anti-Co a have been reported, although both are known to occur with severe morbidity; anti-Co b is relatively rare and often found in patient's sera containing other alloantibodies. In vivo studies have shown that anti-Co a and anti-Co b antibodies are able to reduce the survival of targeted erythrocytes [19][20][21][22][23]. There are also reports of auto-antibodies mimicking Colton specificities [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Τhe pathophysiological relevance of reduced AQP1 presence in WM tissue from patients with NMOSD phenotype remains to be proven. As described in Section 2.3, AQP1 contains the Colton blood group antigen expressed on erythrocytes [51], while antibodies against Colton antigens can cause hemolytic diseases [52]. Therefore, it has been argued that if AQP1-Abs existed in NMOSD, they might also cause hemolytic disease, which is absent in NMOSD [56].…”
Section: Are Aqp1-abs In Nmosd Pathogenic?mentioning
confidence: 99%
“…AQP1 contains the Colton blood group antigen expressed on erythrocytes [ 51 ]. Antibodies against Colton antigens are very rare and can cause transfusion reactions or hemolytic disease [ 52 ]. Interestingly, in Section 3.2 we describe a case with high titer of AQP1 antibodies and the development of both autoimmune hemolytic anemia (AIHA) and a clinical relapse in a patient with NMOSD phenotype; recovery of both diseases occurred with a simultaneous dramatic drop of AQP1-Abs.…”
Section: Aqp1mentioning
confidence: 99%